Une exception française : vers un nouveau paradigme de l’enseignement de la philosophie en Terminale ? - Bruno Poucet (Recherches en Éducation)
The French teaching of philosophy has been organized with a special pattern. This pattern is coming before the great revolution. He has been upset along the XIXe siècle and a new one with typical exercises and practices (for example dissertation), a special teacher, is coming on about 1920. This new way of teaching philosophy at school will be leave by a new generation of teachers and because of the transformation of the society. Presently, the French teaching of philosophy is looking for a new pattern.